2021
DOI: 10.1007/s00508-021-01813-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between hypothyroidism and COVID 19?

Abstract: Is there an association between hypothyroidism and COVID 19? 415

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Nevertheless, there is no evidence that the administration of thyroid hormones improves prognosis in those patients. We might also wonder that, in some studies that observed a correlation between thyroid dysfunction and more severe COVID-19 presentation, the alterations in thyroid hormone levels were actually due to NTIS, as opposed to an underlying previous clinical thyroid disease (Bakshi SS, 2021). So, these results have to be carefully analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is no evidence that the administration of thyroid hormones improves prognosis in those patients. We might also wonder that, in some studies that observed a correlation between thyroid dysfunction and more severe COVID-19 presentation, the alterations in thyroid hormone levels were actually due to NTIS, as opposed to an underlying previous clinical thyroid disease (Bakshi SS, 2021). So, these results have to be carefully analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indeed observed that hypothyroidism may be associated with an increased risk for COVID-19 or a poorer prognosis in patients with the disease (Zhang Y, 2020;Bakshi SS, 2021). However, these studies are limited due to small sample sizes and lack of comparison with patients without hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…We might also wonder that, in some studies that observed a correlation between thyroid dysfunction and more severe COVID-19 presentation, the alterations in thyroid hormone levels were actually due to NTIS, as opposed to an underlying previous clinical thyroid disease. 9 So, these results have to be carefully analysed.…”
Section: Discussionmentioning
confidence: 99%
“…11 The other previous cohort studies and case series were also limited by small sample sizes and lack of controls. 8,9,11,13,31,43,44 In the present study, a caliper width of 0.17 was used for the matched analysis. It is considered conservative and restricts the selection of controls which are indeed similar to the cases, as recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation